Eugenia dysenterica extract microencapsulated for application in food (Revista de Ciências Agroveterinárias, 2025)
Eugenia dysenterica DC. is a fruit of the Cerrado that has great economic potential for both food and medicinal applications. Its phytochemical composition has potential health benefits, especially the phenolic compounds, which have significant antioxidant activity. However, being highly reactive, they can lose their stability and function under certain specific conditions, affecting their antioxidant potential. This study aimed to develop and characterize microparticles to protect the bioactive compounds present in the leaf of E. dysenterica DC. for application in food. The microparticles were produced using the ionic gelation technique with alginate and pectin (wall materials) and were assessed for morphology, average diameter, humidity, and encapsulation efficiency. The content of phenolic compounds and antioxidant activity was determined for the extract and microparticles. Qualitative analysis of the phenolic compounds and antioxidant activity was carried out by Thin Layer Chromatography (TLC). The microparticles were predominantly spherical in shape and had an average diameter of 46.06 ± 18.81μm, a moisture content of 92.01% and an encapsulation efficiency of 16.10%. When using methanol as the extracting solution, the leaf extract showed a total phenolic compound content of 171.89 mg EAG.100g-1 and antioxidant activity of 91.09%, while the microparticles showed a phenolic compound content of 27.65 mg EAG.100g-1 and antioxidant activity of 34.17%. Qualitative analysis indicated the presence of phenolic compounds and antioxidant activity in the extract, which was not detected in the microparticles. The low concentration of compounds and activity in the microparticles may be associated with the percentage of extract incorporated into the production process, extract concentration, and particle diameter. The concentration of the extract in the production process proves to be an important variable in improving the loading of phenolic compounds, since microencapsulation by ionic gelation has a potential application in foodstuffs as it provides protection for antioxidant compounds, while the size of the microparticles is an important factor in not altering the sensory perception of the food.
Keywords: microparticle; ionic gelation; cagaita; cerrado